PENERAPAN SISTEM INFORMASI PENGGAJIAN KARYAWAN BERBASIS WEB PADA CAFE TEATIME MENGGUNAKAN METODE GROSS - M. Renaldi Wildan F; I Kadek Dwi Nuryana; Ahmad Heru Mujianto; Kistofer, Terdy (Inovate, 2024)
Employees usually receive a fixed salary from the company and can also be interpreted as a motivation toemployees that can be done periodically. The remuneration is made up of basic salary, overtime, and so on.The administration calculates the salaries of employees and the data necessary for the salary calculationprocess such as employee data, employee time accuracy reports, and such reports are obtained through theprocessing of the percentage of employees received when recapitulating the presence and working hours datafrom HRD. In the calculation of salaries, three methods that can be applied by the agencies of the cafe areavailable Net, Gross method, and Gross Up method. The processes that have not been integrated into thesystem including data processing and the process of employee wage calculation are still manual.A summary of the results of this study is a web-based employee remuneration application that can helpinternal cafes such as HRD, admin, general manager, and general manager.Keywords: wage system, gross, information system.